Development of high-copy number plasmids in Pseudoalteromonas haloplanktis TAC125 - Calvanese M.; Balestra C.; Colarusso A.; Lauro C.; Riccardi C.; Fondi M.; Parrilli E.; Tutino M. L. (Applied Microbiology and Biotechnology, 2023)
Abstract: The Antarctic bacterium Pseudoalteromonas haloplanktis TAC125 (PhTAC125) is considered an interesting alternative host for the recombinant protein production, that can be explored when the conventional bacterial expression systems fail. Indeed, the manufacture of all the difficult-to-express proteins produced so far in this bacterial platform gave back soluble and active products. Despite these promising results, the low yield of recombinant protein production achieved is hampering the wider and industrial exploitation of this psychrophilic cell factory. All the expression plasmids developed so far in PhTAC125 are based on the origin of replication of the endogenous pMtBL plasmid and are maintained at a very low copy number. In this work, we set up an experimental strategy to select mutated OriR sequences endowed with the ability to establish recombinant plasmids at higher multiplicity per cell. The solution to this major production bottleneck was achieved by the construction of a library of psychrophilic vectors, each containing a randomly mutated version of pMtBL OriR, and its screening by fluorescence-activated cell sorting (FACS). The selected clones allowed the identification of mutated OriR sequences effective in enhancing the plasmid copy number of approximately two orders of magnitude, and the production of the recombinant green fluorescent protein was increased up to twenty times approximately. Moreover, the molecular characterization of the different mutant OriR sequences allowed us to suggest some preliminary clues on the pMtBL replication mechanism that deserve to be further investigated in the future. Key points: • Setup of an electroporation procedure for Pseudoalteromonas haloplanktis TAC125. • Two order of magnitude improvement of OriR-derived psychrophilic expression systems. • Almost twenty times enhancement in Green fluorescent protein production.